2015
DOI: 10.4236/ojog.2015.55042
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Bacteriuria in Pregnant Women in the Antenatal Booking Clinic at Aminu Kano Teaching Hospital, Kano, Nigeria

Abstract: Asymptomatic bacteriuria is common in pregnant women and if untreated could lead to serious complications. Despite this, its prevalence and microbiological characteristics have not been well studied in Kano and they vary among different populations. The objective of the study was to determine the prevalence, microbiological characteristics and pregnancy outcome of asymptomatic bacteriuria in pregnancy among women who came for antenatal booking clinic at the Aminu Kano Teaching Hospital (AKTH) Kano. A cross sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 15 publications
5
10
1
1
Order By: Relevance
“…We noticed that the prevalence rate of ASB is varied in different studies. Our finding was found higher than other studies conducted in different parts of Ethiopia (10.6–11.5%) [ 27 , 32 , 33 ], and elsewhere in other African countries at (7.3–14.7%) [ 3 , 4 , 34 – 36 ], Chandanaish, Bangladesh at (13%) [ 5 ], and Sanandaj, Iran at (8.9%) [ 7 ]. However, our report was found almost comparable with other reports in Ethiopia that reported ASB between 16% and 18.9% [ 29 , 37 , 38 ] and abroad in Sagamu, Nigeria (23.9%) [ 39 ].…”
Section: Main Textcontrasting
confidence: 80%
“…We noticed that the prevalence rate of ASB is varied in different studies. Our finding was found higher than other studies conducted in different parts of Ethiopia (10.6–11.5%) [ 27 , 32 , 33 ], and elsewhere in other African countries at (7.3–14.7%) [ 3 , 4 , 34 – 36 ], Chandanaish, Bangladesh at (13%) [ 5 ], and Sanandaj, Iran at (8.9%) [ 7 ]. However, our report was found almost comparable with other reports in Ethiopia that reported ASB between 16% and 18.9% [ 29 , 37 , 38 ] and abroad in Sagamu, Nigeria (23.9%) [ 39 ].…”
Section: Main Textcontrasting
confidence: 80%
“…The prevalence in this study is comparable to that reported in Nigeria, 14 but lower than studies from Ethiopia. [28][29][30][31] These discrepancies between and within countries may be due to differences in the study participants' socioeconomic levels, and cultural 7 and religious behaviours related to personal hygiene and sexual contact.…”
Section: Discussionsupporting
confidence: 78%
“…4 In contrast, a high proportion of S. saprophyticus was reported from Bahir Dar, Ethiopia (48.2%) 29 and Nigeria (44.5%). 3 In the current study, participants with the previous history of UTI had about 3 times chance of developing ASB (p=0.004). A similar finding was reported from Gondar, Ethiopia 30 and Egypt.…”
Section: Discussionmentioning
confidence: 55%
“…Urinary tract infection (UTI) is an infection of the urinary tract system; it can occur both in the community and hospital environment. 1,2 Even though all age groups are affected by UTI, pregnant women, [3][4][5] and immuno-compromised individuals 6 are more susceptible. Generally, women are at greater risk of UTI as compared to males because of anatomical position and short urethra.…”
Section: Introductionmentioning
confidence: 99%